Трематоды рода Allocreadium Lооss, 1900 в рыбах семейства Cobitidae водоемов Украины - Коваль, В.П.; Изюмова, Н.А. (Вестник зоологии, 1972)
In fish of the Cobitidae family from basins of the Azov and Black seas, besides Allocreadium transversale (R u d., 1802), A. baueri S p a s s k y et R o y t m a n, 1960, subsp., cobiti subsp. n. is also met. The new subspecies is found in Cobitis taenia L. from the rivers Dnieper, Seversky Donets, Tisa. The body length is 1.4-2.7 mm, maximum width — 0.4-0.8 mm. The ratio between the ventral and oral sucker is 1 : 1.5-2. As com¬pared with typical forms of A. baueri the new subspecies has a longer oesophagus reaching the level of the ventral sucker posterior third part; the pharynx is less as compared with the oral sucker (the ratio between the pharynx length and oral sucker length is 1 :2.5 whereas in the typical forms of A. baueri it is equal to 1 : 1.5-1.7); the testicles are lo¬cated farther from the ovary and nearer to the posterior end of the body; the testicle sizes are relatively smaller.